(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
: Pile construction activities is a multifaceted activity among the construction activities that are performed by heavy machines, materials and energy sources generating environmental impacts associated with pilling activities such as carbon emissions, noise, heavy vibration, soil instability and groundwater pollution. Sustainable piling construction guarantees that the whole piling process meets environmental sustainability and ultimately human health and wellbeing. Data were gathered through a questionnaire survey administered to construction professionals including engineers, project managers, surveyors, and builders. Out of the 50 questionnaires distributed, 41 responses were analyzed. The study employed the Relative Importance Index (RII) to rank the effectiveness of various strategies in mitigating environmental impacts. The findings underscore the critical role of introducing low-emission machinery and optimizing operational hours in reducing carbon emissions. Noise management was most effectively achieved through alternative pile installation methods combined with regular equipment maintenance. Maintaining adequate setbacks from structures and employing controlled installation techniques were identified as essential strategies to mitigate vibration. Addressing soil instability was found to rely heavily on thorough site investigations and the implementation of effective ground stabilization techniques and preventing groundwater pollution requires the proper use of drilling fluids and diligent site management. These findings contributed to the development of environmentally sustainable practices in pile construction, emphasizing the importance of comprehensive strategies to mitigate the adverse environmental impacts of such activities in Nigeria.